2023
DOI: 10.15560/19.4.589
|View full text |Cite
|
Sign up to set email alerts
|

The hitchhiker’s guide to Australia: the 18,000-km-long journey of Alepia viatrix Jaume-Schinkel, Kvifte, Weele & Mengual, 2022 (Diptera, Psychodidae) discovered through citizen science

Santiago Jaume-Schinkel,
Ximo Mengual,
Andy G. Howe
et al.

Abstract: The Neotropical genus Alepia Enderlein, 1937 (Diptera, Psychodidae) is newly recorded in Australia. We present new geographical records for Alepia viatrix Jaume-Schinkel, Kvifte, Weele & Mengual, 2022, extending the range of this species by 18,000 km. We attribute these new Australian records to the likely unintentional introduction of A. viatrix through international bromeliad trade. This moth fly was found by school children working with insect taxonomists through an Australian citizen-science project, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…These findings demonstrate the power of citizen-science initiatives in uncovering previously unknown distribution patterns and expanding our understanding of species ranges ( Barahona-Segovia et al 2022 , Jaume-Schinkel and Mengual 2022 , Jaume-Schinkel et al in press ). The integration of citizen-science initiatives has proven to be an invaluable asset in advancing our understanding of species distribution patterns ( Barahona-Segovia and Barceló 2021 ).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…These findings demonstrate the power of citizen-science initiatives in uncovering previously unknown distribution patterns and expanding our understanding of species ranges ( Barahona-Segovia et al 2022 , Jaume-Schinkel and Mengual 2022 , Jaume-Schinkel et al in press ). The integration of citizen-science initiatives has proven to be an invaluable asset in advancing our understanding of species distribution patterns ( Barahona-Segovia and Barceló 2021 ).…”
Section: Discussionmentioning
confidence: 66%
“…Citizen-science projects can provide a more accurate picture of the real distribution of species. Previous studies by Maistrello et al (2016) , Alaniz et al (2018) , Dörler et al (2018) , Barahona-Segovia and Barceló (2021) , Jaume-Schinkel and Mengual (2022) , Kvifte (2023) , Jaume-Schinkel et al (in press) have highlighted the importance of citizen science in capturing species distribution data. In our study, we found two new records for The Netherlands through a citizen-science project, adding valuable information to the existing knowledge base.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in many other taxa, citizen science has contributed towards decreasing the shortfall in spatial occurrences for thousands of species, and flies are no exception. Our knowledge of the extent of occurrence of both tiny and inconspicuous flies as well as large and striking flies has increased thanks to biodiversity platforms such as iNaturalist and Facebooks groups devoted to flies (e.g., Barahona‐Segovia et al., 2023 ; Clem et al., 2023 ; Jaume‐Schinkel, Kvifte, et al., 2023 , Jaume‐Schinkel, Mengual, et al., 2023 ). Furthermore, Clem et al.…”
Section: Discussionmentioning
confidence: 99%
“…As in many other taxa, citizen science has contributed towards decreasing the shortfall in spatial occurrences for thousands of species, and flies are no exception. Our knowledge of the extent of occurrence of both tiny and inconspicuous flies as well as large and striking flies has increased thanks to biodiversity platforms such as iNaturalist and Facebooks groups devoted to flies (e.g.,Barahona-Segovia et al, 2023;Clem et al, 2023;Jaume- Schinkel, Kvifte, et al, 2023, Jaume-Schinkel, Mengual, et al, 2023.Furthermore,Clem et al (2023) demonstrated that citizen science can be a key player in expanding the known range of flies at the local level. Here, the northern limit of H. clausa-an endemic fly of the Sub-Antarctic Ecoregion-has extended from the Cape Horn Archipelago to the Torres del Paine National Park.…”
mentioning
confidence: 99%